Hierarchical Control of a Quadcopter under Stuck Actuator Fault. Issue 2 (2020) - Nguyen, Ngoc Thinh; Prodan, Ionela; Petzke, Felix; Streif, Stefan; Lefèvre, Laurent
Abstract: We propose a hierarchical FTC (Fault Tolerant Control) scheme for trajectory tracking by a quadcopter system under stuck actuator fault and actuator saturation. Both the FDI (Fault Detection and Isolation) and control reconfiguration modules are implemented at the low-level associated with the rotation dynamics through a NMPC (Nonlinear Model Predictive Control) strategy. The uncontrolled (when under fault) yaw torque is predicted and compensated by the NMPC. It is shown that the overall control scheme succeeds in maintaining trajectory tracking for various fault events (both in the sense of having various stuck values and in the sense of changing the actuator under fault).